Discoursal Variation and Gender: The Case of Compliment Responses Among Male and Female Persian Speakers - Shahreza, Mohammad Ali Heidari; Dastjerdi, Hossein Vahid; Marvi, Sepideh (Mediterranean Journal of Social Sciences, 2011)
This study was aimed at investigating the discoursal variation of compliment responses (CRs) among male and female IranianPersian speakers. A total of 60 elementary Iranian teenage EFL learners participated in the study. The data were collected through theapplication of written discourse completion tasks (DCTs), with four situations, i.e. appearance, character, ability and possession. Theanalysis of the data showed that both male and female groups mostly preferred Accept strategies in almost all the four situations; however,female participants took side with Evade strategies when receiving compliments for possession. The findings have generally a practicalrelevance to the speech communities under study by providing guidelines for the use of CRs. They have also pedagogical implications,helping males and female Persian speakers respond to compliments in a culturally acceptable manner.